Mathematical Modeling and Controller for PV System by Using MPPT Algorithm - Issa, H. I.; Mohammed, H. J.; Abdali, L. M.; Al Bairmani, A. G.; Ghachim, M. (Вестник ИжГТУ имени М.Т. Калашникова, 2021)
In this research, the study theory of system includes the use of an important source of renewable energy sources (solar source) and linking this system with an electrical load. The world is witnessing a significant rise in fossil fuel prices since the ending of the 20th century and now, this rise in price increases with the decrease in inventory day after day. Therefore, it turned that the field of attention to researchers of power generation to expand in non-conventional energy sources (new and renewable energy sources). New and renewable energy is inexhaustible in use because they rely on renewable natural resources. The mathematical model is an important part of the detailed study for PV systems. As well as study models for photovoltaic systems via the MATLAB/Simulink, this programming environment contains many models for renewable systems intended to perform simulation and analysis. Solar cells system needs to apply the MPPT algorithm due to the instability of external circumstances such as solar radiation and temperature. At a constant temperature of 25 °C, as the radiation level increases, the current and voltage of the module increase, this leads to an increase in output power. At a constant radiation level of 100 W/m2, as the module temperature increases, the current increases and the voltage decreases, this causes the output power to decrease. The maximum power is reached at 17 V and 3.5 A by the MPPT method. The Perturb and Observe algorithm is used to achieve maximum power.